Financial Management to Improve Quality of Education - Siska Yulia Weny; Normala Rista (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The quality of education is influenced by various factors, one of which is the financial aspect. Finance has a vital role in supporting the improvement of the quality of madrasa education. This study aims to analyze financial management at Madrasah Tsanawiyah Raudlatut Thalabah and its contribution to improving the quality of education. The focus of the research includes: (1) planning madrasah financial management, (2) implementation of madrasah financial management, and (3) evaluation of madrasah financial management in improving the quality of education. This research uses a qualitative method with a case study approach. Data collection techniques include observations of madrasah activities and conditions, interviews with the madrasah principal, treasurer, and curriculum vice principal, as well as documentation to strengthen data validity. Data was analyzed through data reduction, data presentation, and drawing conclusions, and its validity was tested using triangulation techniques. The results of the study show that: (1) financial planning is carried out in a structured manner through Madrasah Self-Evaluation (EDM) for the preparation of RKAM, involving various stakeholders; (2) financial implementation is transparent and accountable, with recording through the General Cash Book, Microsoft Excel, and monitoring based on the e-RKAM application; and (3) evaluations and internal audits are carried out periodically to ensure the effectiveness of fund use and the accuracy of financial reports.